Representation of women’s roles in American funeral industry in Buried by the Bernards - Anggi Puspitasari (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2024)
Following the Civil War, the funeral industry in the United States excluded women from the job of taking care of the deceased. But in the last 10 years, women have taken their place in the funeral industry again. This can be seen from the data recently that shows that 65% of funeral director program graduates are women. The role of women in the funeral industry can also be seen in one of the reality series on Netflix, Buried by the Bernards. Therefore, this research aims to analyze how the role of women in the funeral industry is represented in Buried by the Bernards. The series portrays the Bernards funeral home, managed by the Bernards family members. Three of whom are women, including Deja, Reagan, and Debbie. To answer the research question, the researcher used Hall’s representation theory. This research employs a descriptive qualitative approach with primary data from the Buried by the Bernards Netflix reality series, and secondary data from books, theses, journals, articles, and online sources. The results of this research show that the American traditional belief that women are unable to work in funeral homes is not true. Based on Buried by the Bernards, women are portrayed as taking an important part in the funeral industry and their status as women does not prevent them from working in the funeral industry. Thus, researcher conclude that women can once again prove that they are equal and their abilities are not inferior to men, even in the funeral industry.